Boxes of hopes, dreams and sacrifices - Tolentino, Jamia Mei E.; Abaya, Leo Antonio C. (Quezon City College of Fine Arts, University of the Philippines Diliman, 2019)
In my thesis, I brought together representational images, with inspiration from analytical cubism and expressionism, and balikbayan boxes to create a narrative on the experiences of families affected by OFW Diaspora.

An OFW leaves for another country for employment to improve the family's financial condition. My father left for abroad when I was 3 years old. It was after 10 years when I saw him again. Now, I haven't been with him for 5 years. He was not present in all occasions and milestones in my life but he tries to connect with us through calls, letters, and balikbayan boxes. Growing up without him by our side, I don't know what his whole identity or personality is like. I only know him through fragments of information and stories we share.

This is a presentation of our experiences as children who grew up without a father or a husband for my mother by our side. I have used images that are whimsical to represent personal experiences, milestones, dreams and childhood. These are the times we wished my father was at our side. The balikbayan boxes represents our connection. They are arranged in a totem-like figure that aims-to recall and commemorate significant events. This is a reimagination of the classic totem within the context of a modern story and design approach.
Thesis (Bachelor of Fine Arts in Painting)
Bibliography: leaves 26-28
Keywords: Cardboard art; Children of foreign workers -- Philippines; Absentee fathers -- Philippines; Totems